(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article analyses various sources of origin of phraseological units with proper nouns in the English language. Proper noun as a component of a phraseological unit is one of the representatives of culture and performs the function of storing and transmitting traditions, history, and culture of people, that is why it is a special linguistic sign. Etymology being one of the crucial issues in studying proper names in phraseological units, it is closely related to semantics of such phraseological units. From the perspective of nature of their genesis the phraseological units in this article are classified into deterministic and indeterministic phraseological units. Etymological and semantic analyses conducted in this article indicate that proper names in phraseological units have historical, literary, and cultural associations.